2013
DOI: 10.1093/ndt/gft039
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin: another bone-related protein related to all-cause mortality in haemodialysis?

Abstract: Our data show that high circulating sclerostin levels are associated with improved survival and suggest that a low bsAP activity may be in the causal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 41 publications
15
96
4
2
Order By: Relevance
“…Lower sclerostin serum levels were identified as independent determinants of VC in patients with chronic kidney disease not yet on dialysis, thus it was suggested that circulating sclerostin may be a protective factor for the progression of VC (35). Consistent with this, higher sclerostin levels have been associated with a reduced mortality in hemodialysis patients (36).…”
Section: Clinical Studymentioning
confidence: 82%
See 1 more Smart Citation
“…Lower sclerostin serum levels were identified as independent determinants of VC in patients with chronic kidney disease not yet on dialysis, thus it was suggested that circulating sclerostin may be a protective factor for the progression of VC (35). Consistent with this, higher sclerostin levels have been associated with a reduced mortality in hemodialysis patients (36).…”
Section: Clinical Studymentioning
confidence: 82%
“…A reduced bone formation as a consequence of reduced osteoblast activity has been identified as the mean pathogenetic effect or for low bone mineral density (BMD) in subjects with T1DM (1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39). intimal thickening in atherosclerosis, and Wnt/b-catenin signaling is a regulator of VSMC behavior (9).…”
Section: Introductionmentioning
confidence: 99%
“…Viaene et al [50] showed that in patients on haemodialysis, the serum concentration of sclerostin is higher than in general population. In the future, these data will be repeatedly confirmed by the results of other studies devoted to identify the role of sclerostin in patients on regular haemodialysis [23,49].…”
Section: The Relation Of Fgf-23 Klotho and Sclerostin With Cardiovasmentioning
confidence: 99%
“…77 In hemodialysis patients, serum sclerostin levels were found to be inversely associated with mortality, 78 raising concerns about the long-term cardiovascular safety of sclerostin inhibition. Further investigation is needed in order to address this critical issue and shed more light on the potential effects of sclerostin on the vasculature.…”
Section: Discussionmentioning
confidence: 99%